2018
DOI: 10.1177/0021998318754641
|View full text |Cite
|
Sign up to set email alerts
|

Panel flutter of curvilinear composite laminated plates in the presence of delamination

Abstract: The effect of variable fiber placement angle on the supersonic linear flutter of rectangular composite panels containing square delamination zone is investigated using an enhanced spline version of finite strip method (FSM). The location dependent stiffness characteristics and mass matrices due to variable fiber orientation angles within every ply are extracted. The structural formulation is based on the higher-order shear deformation theory while the first-order piston theory is utilized to predict the loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…From above analyses, it can be found that in previous studies on the flutter characteristics of the composite laminated panels, the fibers were laid along a straight line. To further improve the aeroelastic stability of the composite laminated panels, the flutter characteristics of composite laminated panels with curvilinear fibers have recently attracted the attentions of scientists 216–218 . For example, the flutter characteristic of a cantilever composite laminated panel with curvilinear fibers in supersonic airflow was studied by Camacho et al 217 As displayed in Figure 14, the orientation of the curvilinear fibers was defined by three functions, and the influences of the fiber orientation on the flutter bounds of the composite laminated panels were analyzed.…”
Section: Research Status Of Aeroelastic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…From above analyses, it can be found that in previous studies on the flutter characteristics of the composite laminated panels, the fibers were laid along a straight line. To further improve the aeroelastic stability of the composite laminated panels, the flutter characteristics of composite laminated panels with curvilinear fibers have recently attracted the attentions of scientists 216–218 . For example, the flutter characteristic of a cantilever composite laminated panel with curvilinear fibers in supersonic airflow was studied by Camacho et al 217 As displayed in Figure 14, the orientation of the curvilinear fibers was defined by three functions, and the influences of the fiber orientation on the flutter bounds of the composite laminated panels were analyzed.…”
Section: Research Status Of Aeroelastic Analysismentioning
confidence: 99%
“…For example, the flutter characteristic of a cantilever composite laminated panel with curvilinear fibers in supersonic airflow was studied by Camacho et al 217 As displayed in Figure 14, the orientation of the curvilinear fibers was defined by three functions, and the influences of the fiber orientation on the flutter bounds of the composite laminated panels were analyzed. In addition, Fazilati 218 analyzed the combined effects of curvilinear fiber orientation and delamination zone on the flutter behaviors of a rectangular composite laminated panel.…”
Section: Research Status Of Aeroelastic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly large numbers of theoretical studies were devoted to the study of plates and shells in a supersonic gas flow (Dowell, 1970;Fazilati, 2018;Merrett & Hilton, 2010;Vedeneev, 2012). In these references, flutter problems were mainly solved in an elastic statement.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have been reported in the literature, in which VSCL could be designed to improve buckling resistance [11], reduce stress concentrations around holes [12], maximize the fundamental natural frequency [13], and optimize aeroelastic characteristics of a composite wing structure [14][15][16][17]. The work of Fazilati [18] presents the effect of delamination in the panel flutter behavior. However, some practical limitations must still be addressed.…”
Section: Introductionmentioning
confidence: 99%